RANCANG BANGUN SISTEM PEMILIHAN BIDANG DAN MINAT KERJA DENGAN TEORI MBTI BERBASIS ANDROID - Fransciska Karundeng; Syaiful Rahman; Izmy Alwiah Musdar (STMIK KHARISMA Makassar, 2018)
Getting a job that suits the personality of the self is the thing that everyone wants. This Final Project discusses the design of psychological test application based on personality theory of Myers and Briggs Type Indicator (MBTI) for job field determination and interest and job recommendation with Android based programming. The purpose of this research is to implement the theory of MBTI into the form of Android-based applications to assist users in identifying their MBTI personality types. After completing the test, the application will display psychotest results describing the behavior, habits, strengths and weaknesses of respondents and their character types based on four dimensional comparisons of MBTI theory: Extrovert-introvert, Sensing-Intuition, Thinking-Feeling, and Judging-Perceiving. The app will also feature personality characteristics, development suggestions, and field work alongside. recommendation of vacancy appropriate to the MBTI type of personality.